1999
DOI: 10.1073/pnas.96.17.9660
|View full text |Cite
|
Sign up to set email alerts
|

Human eosinophils regulate human lung- and skin-derived fibroblast propertiesin vitro: A role for transforming growth factor β (TGF-β)

Abstract: Eosinophils have been associated with fibrosis. To investigate their direct role in fibrosis, human peripheral blood eosinophil sonicate was added to human lung or dermal fibroblasts, and proliferation ([ 3 H]thymidine) and collagen synthesis ([ 3 H]proline) were evaluated. Proliferation was enhanced significantly in the monolayers in a dosedependent manner. The activity of the eosinophil fibrogenic factor(s) remained unaltered when heated (56°C, 30 min). Supernatants of cultured eosinophils (20 min or 18 hr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
152
2
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(164 citation statements)
references
References 46 publications
(56 reference statements)
5
152
2
4
Order By: Relevance
“…Indeed, in humans, inhalation of rIL-5 in patients with asthma increased airway eosinophilia, sputum eosinophil cationic protein levels, and AHR (45), suggesting that IL-5 alone is sufficient to activate human eosinophils and to induce physiological changes in the airways. On the other hand, like human eosinophils (39,40), mouse eosinophils produced TGF-␤1 and retained their ability to up-regulate TGF-␤1 production in response to IL-5 and IL-3 (Fig. 4A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in humans, inhalation of rIL-5 in patients with asthma increased airway eosinophilia, sputum eosinophil cationic protein levels, and AHR (45), suggesting that IL-5 alone is sufficient to activate human eosinophils and to induce physiological changes in the airways. On the other hand, like human eosinophils (39,40), mouse eosinophils produced TGF-␤1 and retained their ability to up-regulate TGF-␤1 production in response to IL-5 and IL-3 (Fig. 4A).…”
Section: Discussionmentioning
confidence: 99%
“…In human asthma, activated eosinophils are a major source of TGF-␤1 by in situ hybridization (19) and immunohistochemistry (20). Isolated human eosinophils produce both TGF-␤1 protein (39) and TGF-␤1 bioactivity (40). Eosinophil-derived TGF-␤1 activity may not be limited to inhibiting AHR, but it may extend to immunoregulation, wound healing, tissue repair, and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Among cytokines implicated in myofibroblast differentiation, TGF␤ has been proven to directly induce ␣-SMA expression in vivo and in vitro (Desmoulière et al, 1993;Rønnov-Jessen and Petersen, 1993). A series of studies with the use of free-floating collagen gels reported TGF␤-induced fibroblast contraction, but did not consider the expression of ␣-SMA (Montesano and Orci, 1988;Finesmith et al, 1990;Tingstrom et al, 1992;Pena et al, 1994;Riikonen et al, 1995;Levi-Schaffer et al, 1999) with two exceptions (Arora and McCulloch, 1994;Kurosaka, 1995;2154). However, it was shown recently that the mechanisms of mechanically unloaded free-floating gel reduction considerably differ from stressed gel contraction (for review see Grinnell, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…20 Some of the eosinophil mediators, such as transforming growth factor-beta, IL-4, IL-6, tumor necrosis factor-alpha, ECP and major basic protein can be fibrogenic. 21 Interestingly, of these factors, transforming growth factor-beta has been reported to enhance in vitro calcification of vascular cells. 22 Finally, eosinophils synthesize and release bioactive mediators, such as leukotriene C4, a potent stimulant of vasoactivity and smooth muscle contraction, and they can induce the release of a number of vasoactive substances, including histamine, prostaglandin D2 and leukotrienes C4 and D4, from mast cells and basophils.…”
mentioning
confidence: 99%